FINANCIAL RESILIENCE STRATEGY AGAINST THE THREAT OF ECONOMIC RECESSION IN MSMEs IN KEC. REPLACE - Widya Novita Sari; Dita Fitriani; Indri Widya Wulandari; Maria Yovita R Pandin (Lumbung Pare Cendekia, 2023)
The purpose of this study is to develop a financial resilience strategy for MSMEs in overcoming the threat of an economic recession. This study uses descriptive analysis with a qualitative approach. The population of this research is UMKM in Kec. Instead, the sample from the study amounted to 4 informants from 93 MSMEs with different types of businesses. Data collection techniques through observation and interviews. The results of this study indicate that the financial resilience strategy has an important role in the development of the MSME economy in Kec. Replace, because with a good and correct financial resilience strategy it can keep business finances running stable. MSMEs are also believed to have high economic resilience so that they can become a support for the financial system and economic stability.